Strategi Bertanya Guru dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar - MG. Rini Kristiantari (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2009)
Abstract: The objective of the current study is to identify teachers’ strategies in questioning  in the learning of Indonesian in elementary schools. This is a qualitative study utilizing a case study design.The research data are collected from teachers and elementary school students of grade IV using field notes on teachers’ strategies in questioning, which were then transcribed. The researcher acted as the key instrument for data collection in this study. The results reveal that teachers have a varied strategies of questioning. On the category of frequency of occurence, teachers tend to employ ‘what’ as a questioning strategy. Teachers’ strategies in questioning also have a variety of functions among others to ask for information, to explain, to emphasize, to beg, to command and to express themselves. The teachers utilized strategies in questioning and responding to the students based on the principles of good questioning and responding to the students.